Synchronization in Singing Duo Performances: The Roles of Visual Contact and Leadership Instruction - D'Amario, Sara; Daffern, Helena; Bailes, Freya (Frontiers in Psychology, 2018)
Interpersonal synchronization between musicians during ensemble performances is characterized by continuous micro-timing adjustments due to intentional and unintentional factors supporting expressive interpretations, or caused by noise during the cognitive-motor process. Whether visual contact between musicians and the instruction to act as leader or follower affect synchronization in ensembles remains mostly unclear. This study investigates the role of visual cues and leader-follower relationships in singing performances. Twelve vocal duos took part in the study, singing a two-part piece, which was composed for the study and was mostly homophonic in structure. Four conditions were applied in a randomised order: with and without visual contact, and with a designated leader or follower. The piece was repeated four times in each condition, and the condition presented three times, for a total of 12 performances of the piece in each condition. Data were acquired using electrolaryngograph electrodes and head mounted microphones to track the fundamental frequency estimates of the individual singers. Results show that the presence and absence of visual contact had a significant effect on the precision and consistency of synchronization during singing duo performances. Precision and consistency were better in the presence of visual contact between singers than without, and these effects were associated with the beginning of phonation of the first note of the piece. The presence/absence of visual contact also had an effect on the tendency to lead or lag a co-performer associated with the onset of the first note; the extent of leading was greater when visual contact was absent. The instruction to act as leader or follower did not affect precision or consistency of synchronization, nor did it relate to the observed tendency to precede or lag a co-performer. The results contribute to the tailoring of rehearsal strategies, as singers and directors can be better informed of the factors influencing synchronisation and focus on specific areas of difficulty in certain performance conditions, such as first note onsets when performers are not able to see each other.